Technical Assistance in Making Instructional Learning Media for Teachers and Students Mas Dr. H. Abdullah Ahmad PGAI Padang - Ade Irma Suryani; Trina Febriani; Yuherman; Rika Nofitri Wulandari; Fitri Rahma Widia; Gusnita Sri Wulandari (PT FORMOSA CENDEKIA GLOBAL, 2022)
Utilization of relevant learning media in the classroom can optimize the learning process. For lecturers, media helps concrete concepts or ideas and helps motivate active learning participants. For students, the media can be a bridge for critical thinking and action. Thus the media can help the task of lecturers and students achieve the specified basic competencies. So that learning media can be used properly, teachers need to know their learning needs and the problems faced by students regarding the material to be taught. To improve the teaching and learning process, a teacher should use instructional media as a channel. Through this channel, the stimulus is delivered to students to motivate, attract attention, stimulate student responses and others. For this purpose, it is necessary for the teacher to know the types of media besides being able to choose, it is also possible to combine several media to convey his meaning.